Expression and functional analysis of the plant-specific histone deacetylase HDT701 in rice - Zhao, Jinhui; Zhang, Jianxia; Zhang, Wei; Wu, Kunlin; Zheng, Feng; Tian, Lining; Liu, Xuncheng; Duan, Jun (Frontiers in Plant Science, 2015)
Reversible histone acetylation and deacetylation at the N-terminus of histone tails play a crucial role in regulating eukaryotic gene activity. Acetylation of core histones is associated with gene activation, whereas deacetylation of histone is often correlated with gene repression. The level of histone acetylation is antagonistically catalyzed by histone acetyltransferases citation(HATs) and histone deacetylases (HDACs). In this work, we examined the subcellular localization, expression pattern and function of HDT701, a member of the plant-specific HD2-type histone deacetylase in rice. HDT701 is localized at the subcellular level in the nucleus. Histochemical GUS-staining analysis revealed that HDT701 is constitutively expressed throughout the life cycle of rice. Overexpression of HDT701 in rice decreases ABA, salt and osmotic stress resistance during seed germination. Delayed seed germination of HDT701 overexpression lines is associated with decreased histone H4 acetylation and down-regulated expression of GA biosynthetic genes. Moreover, overexpression of HDT701 in rice enhances salt and osmotic stress resistance during the seedling stage. Taken together, our findings suggested that HDT701 may play an important role in regulating seed germination in response to abiotic stresses in rice.